A case of feline gastrointestinal eosinophilic sclerosing fibroplasia associated with phycomycetes - Grau-Roma, Llorenc; Galindo-Cardiel, I.; Isidoro-Ayza, M.; Fernández, M.; Majó, N. (Elsevier, 2014)
Feline gastrointestinal eosinophilic sclerosing fibroplasia (FGESF) is a recently described inflammatory condition of domestic cats with unknown aetiology. A proportion of cases of FGESF are associated with bacteria, but antibiotic treatment is ineffective. It has been hypothesized that genetically predisposed cats may develop FGESF in response to the introduction of bacteria or other antigens into the intestinal wall. A 9- month-old male Persian cat presented with a history of marked acute haematemesis. A mass (10 cm diameter) was detected within the pylorus and proximal duodenum and this was not surgically accessible. On necropsy examination the duodenal wall was seen to be markedly thickened with extensive mucosal ulceration. Microscopically, there were haphazardly oriented trabecular bands of dense eosinophilic collagen,separated by wide, clear areas containing variable numbers of fibroblasts, eosinophils, mast cells, neutrophils,macrophages, lymphocytes and plasma cells. Numerous pleomorphic, non-parallel walled, sparsely septate hyphae, characteristic of phycomycetes, were present within the collagen matrix. Colonies of gram-positive and gram-negative rods were also present within the lesion. This is the first description of FGESF with intralesional fungi.